Microstructure of nitrided and nitrocarburized layers produced on a superaustenitic stainless steel - Fernandes, Frederico Augusto Pires; Casteletti, Luiz Carlos; Gallego, Juno [UNESP] (Elsevier, 2013)
The expanded austenite γN can be produced in austenitic stainless steels by plasma nitriding, carburizing or nitrocarburizing at low temperatures. This metastable phase presents higher hardness and toughness if compared with traditional nitride layers whilst also maintaining the corrosion resistance. However, the application of plasmas composed by both nitrogen and carbon is technologically recent and the effect of such process on the microstructure and properties of the nitrocarburized layers is still under investigation. In this study, samples of UNS S31254 superaustenitic stainless steel were produced by plasma nitriding and nitrocarburizing at 400 C, 450 C and 500 C for 5 h. The plasma treated samples were observed by optical and transmission electron microscopy and also analyzed by X-ray diffraction. The thickness of the layers increased with temperature and the nitrocarburized layers were thicker than nitrided at a given temperature. The presence of expanded austenite was confirmed by X-ray diffraction through its characteristic anomalous shift on the diffracted peaks related to the austenite. Nitride formation on samples produced at 400 C was only identified by transmission electron microscopy where fine rounded particles with 10-15 nm size revealed reflections consistent with the CrN cubic chromium nitride. The estimated lattice parameter from the expanded austenite ranged from 0.38 to 0.41 nm depending on the employed {h k l} reflection which was found to be 6-11% larger than the untreated austenite lattice parameter. © 2013 Brazilian Metallurgical, Materials and Mining Association.
Keywords: Expanded austenite; Microstructure; Nitriding; Nitrocarburizing; Superaustenitic stainless steel; Transmission electron microscopy